THE RESOURCE CURSE HYPOTHESIS - Pankaj Khandelwal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The abundance of natural resources is often considered a key driver of a country’s economic growth and development. Resource-rich nations are believed to benefit from increased investment, accelerated industrialization, and expanded employment opportunities, fuelled by the rents generated from these resources. However, academic literature highlights a critical insight: possessing abundant natural resources does not necessarily guarantee economic growth. Drawing on vast literature the paper argues that weak institutional quality, rent-seeking behaviour and political distortions often negate the potential benefits of resource wealth. The paper further explores political economy models that explain this phenomenon, including the Dutch Disease effect, centralized and decentralized political economy models and theories such as the Rentier State, Staple Trap, Dependency and Institutional theories. Our analysis highlights the critical importance of transparent governance, accountable institutions and strategic investments in human development to convert natural wealth into inclusive and sustainable growth.